The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2139/ssrn.1315233
|View full text |Cite
|
Sign up to set email alerts
|

A Resolution of the Purchasing Power Parity Puzzle: Imperfect Knowledge and Long Swings

Abstract: Asset prices undergo long swings that revolve around benchmark levels. In currency markets, ‡uctuations involve real exchange rates that are highly persistent and that move in nearparallel fashion with nominal rates. The inability to explain these two regularities with one model has been called the "purchasing power parity puzzle." In this paper, we trace the puzzle to exchange rate modelers'use of the "Rational Expectations Hypothesis." We show that once imperfect knowledge is recognized, a monetary model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
3
12
0
Order By: Relevance
“…The deviations from both the PPP and the UIP conditions exhibited a pronounced persistence that was empirically indistinguishable from a …rst -or sometimes even second -order nonstationary process, whereas a combination of the two was often found to be stationary. This was precisely what early work on a monetary model for exchange rate determination based on imperfect knowledge expectations assumed would be the case (subsequently published in Goldberg, 2007, 2011). As a consequence, it became the beginning of a long collaboration between Roman and Michael on one hand and the econometrics group in Copenhagen on the other.…”
Section: Is In ‡Ation Imported? Analyses Of the International Transmimentioning
confidence: 76%
See 2 more Smart Citations
“…The deviations from both the PPP and the UIP conditions exhibited a pronounced persistence that was empirically indistinguishable from a …rst -or sometimes even second -order nonstationary process, whereas a combination of the two was often found to be stationary. This was precisely what early work on a monetary model for exchange rate determination based on imperfect knowledge expectations assumed would be the case (subsequently published in Goldberg, 2007, 2011). As a consequence, it became the beginning of a long collaboration between Roman and Michael on one hand and the econometrics group in Copenhagen on the other.…”
Section: Is In ‡Ation Imported? Analyses Of the International Transmimentioning
confidence: 76%
“…But, due to other demanding commitments, it took roughly 10 years until I …nalized the ideas in a chapter of the Handbook of Econometrics (Juselius, 2009b). Given the integration properties of the data, the paper demonstrated that a stationary PPP was empirically invalid, a result that was in accordance with the theory of imperfect knowledge economics Goldberg, 2007, 2011). That the PPP needs the UIP to become stationary was subsequently demonstrated in several papers.…”
Section: Confronting Theories With Datamentioning
confidence: 92%
See 1 more Smart Citation
“…Frydman et al . (), solve the PPP puzzle by the use of the IKE hypothesis to explain the long swings in the exchange‐rate path.…”
Section: Vecms and Economic Policymentioning
confidence: 99%
“…As such, CVAR models are instruments that are well suited to confront theoretical results of Imperfect Knowledge Economics (Frydman and Goldberg, ) with empirical evidence (e.g. : Frydman et al ., , ).…”
Section: Introductionmentioning
confidence: 99%